Классификация твердосплавных буровых коронок - Линенко-Мельников, Ю.П. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
In this abstract the classification of hardmetal drilling crowns in different rock-geological conditions and their further application are presented. The methods of drilling and corresponding destruction mechanisms are considered. The main types of energy that flows from instrument to rock and their effective usage are given. The applicable types of hardmetal inserts and the form of their working surface for the known types of drilling crowns are determined.